Exploring the Issues of Open Government Data Implementation in Malaysian Public Sectors - Mustapa, Mimi Nurakmal; Hamid, Suraya; Nasaruddin, Fariza Hanum (Insight Society, 2019)
The paper presents a preliminary study of current progress and the issues of OGD implementation in Malaysia. With this objective, the authors attempt to identify initial factors that influence OGD implementation in the public sectors and discern how far the OGD initiative in Malaysia has grown since its inception. The authors make the highlight of the OGD implementation phase rather than adoption phase due to the research aim is to look at the OGD activities beyond adoption. Adoption phase is where the organization is in the state of deciding whether to adopt an innovation or not, while the implementation phase is the extent where the innovation is taking into actual use. Taking from the perspective of the central agency who is leading the OGD initiative, by using interview, observation, and desk research as the research approaches, the issues pertaining to OGD implementation is consolidated into the technology-organization-environment framework. The findings have indicated that data granularity, culture, policy, resources, skills, incentives, use and participation, and external pressure are the current issues transpired in the OGD implementation. These findings are contributing to the conceptual framework of authors' future works in determining the factors influencing OGD post-adoption in the public sectors. © 2019 Insight Society.